PF-34 A Review of Animal Welfare Protocol on Dog Shelter in Java Area Indonesia - Mariana Kresty Ferdinandez; . Setiawan; Rio Aditya; Karin Helga Franken (Hemera Zoa, 2018)
The number of pet owning in Indonesia, especially in big cities around Java island are highly growing in the past few years.This growing number of pet owning, especially in dogs, unfortunately, has became affected with growing numbers of dog abandonment and mistreated due to irresponsible pet owners issues and lack of law enforcement of animal welfare and animal cruelty law. This affected to growing number of dog shelters around Java island.Although there is still limited resources on the total population of abandoned dogs and dogs shelters in Java, many shelters reported that the numbers of intake and reports to their shelters are increasing.Therefore, it is important the assets animal welfare in a dog shelter environment, to meet the standards of care in a dog shelter.A shelter assessment protocols have been developed to measure the welfare aspects of the shelter by Barnard et al. [1]. In brief, the animal welfare assessment consists of three levels; shelter, pen, and individual level.Shelter level Consist of management based information such as general information, type of housing, feeding, exercise routine, mortality rate. Animal based assessment which is emotional state of the animals were also recorded using Visual Analogue Scale method.Pen level Consist of resource based assessment including space allowance, bedding, evident of sharp edges, and access to water. The animals were also assessed whether there are evident of diarrhea,Individual level Consist of reactions towards humans, body condition score, hygiene, skin condition, lameness, and respiratory problems.